Percolation theory and particle systems proceedings - Roy Rahul ed.; Workshop on Percolation Theory and Particle Systems; Workshop on percolation theory and particle systems New Delhi, India Dec-96 (New Delhi ISI, 1996)
This volume contents the notes of the talks on percolation theory and particle systems.The articles included here may be classified into two groups, such as the mathematical perspective and the physics perspective.
Keywords: Percolation theory; Statistical physics